Ideology of the image in the Albanian films of socialist realism - Hoxha, Lulzim (Advances in Social Sciences Research Journal, 2015)
By means of this paper, I will try to introduce you with a very clear analysis of the important impact of Albanian cinematography, where films like: Mountains covered of green (Malet me Blerim mbuluar) or “The bride and the curfew”(Nusja dhe shtetrrethimi) had an essential role in promoting communist ideology, as well as movies such as „Rambo“, „Full Metal Jacket“ or „Rocky that were also characterized by the reflection of American conservatism in the late 80s, a period that reached its peak with President Reagan coming in power. This analysis will be accomplished through a comparative approach of these kinds of films that publicly show the heroism of a nation as well as a clear boundary between the good and the bad, the hero and the coward, being characterized often by a kind of delirium outbreak of racial superiority. This culture of collective image perceived as art, will be analyzed in ideological field that the culture itself intends to convey to operative mechanisms of images policy. In this theoretical journey, I will rely on analysis that Douglas Kellner made for Hollywood movies in his article: “Films, politics and ideology: Reflections on Hollywood Film in the age of Reagan”.